Proceedings of the 2013 International Conference on Intelligent User Interfaces 2013
DOI: 10.1145/2449396.2449429
|View full text |Cite
|
Sign up to set email alerts
|

Exploring 3d gesture metaphors for interaction with unmanned aerial vehicles

Abstract: We present a study exploring upper body 3D spatial interaction metaphors for control and communication with Unmanned Aerial Vehicles (UAV) such as the Parrot AR Drone. We discuss the design and implementation of five interaction techniques using the Microsoft Kinect, based on metaphors inspired by UAVs, to support a variety of flying operations a UAV can perform. Techniques include a first-person interaction metaphor where a user takes a pose like a winged aircraft, a game controller metaphor, where a user's h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(50 citation statements)
references
References 9 publications
0
48
0
2
Order By: Relevance
“…Pfeil et al [10] have previously developed full body gesture interfaces for controlling an AR Drone using a depth camera and joint information. Multiple metaphors for controlling a UAV were proposed, and a number of interfaces were compared in a formal user study.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Pfeil et al [10] have previously developed full body gesture interfaces for controlling an AR Drone using a depth camera and joint information. Multiple metaphors for controlling a UAV were proposed, and a number of interfaces were compared in a formal user study.…”
Section: Related Workmentioning
confidence: 99%
“…Pfeil et al showed that gestural interfaces were preferred to the packaged smartphone application for the AR Drone with regards to naturalness, fun, and overall preference [10]. For that reason we developed our own simple control configuration using a Nintendo Wiimote.…”
Section: Wiimotementioning
confidence: 99%
See 1 more Smart Citation
“…These types of controllers are neither natural nor intuitive and require long training periods to be mastered [2]. In order to make drones more accessible to non-expert users and facilitate their direct control in demanding tasks such as inspection or rescue missions, several studies have investigated the use of gestures [3], [4]. In a previous study, the authors have identified an intuitive upper body movement pattern that naïve users exploited to fly a fixed wing drone [5].…”
Section: Introductionmentioning
confidence: 99%
“…of smaller aerial robots are envisioned to provide aid in domains including construction [16], utilities [44], search-and-rescue [15], and space [8,9] by performing inspection, mapping, telepresence, and delivery tasks. We term these robots, which are represented in the growing body of research on micro air vehicles (MAVs) and multirotor aircraft [21,32,38], robotic airships [3,6], and space exploration robots [9], "assistive free-flyers" (AFFs).…”
Section: Introductionmentioning
confidence: 99%